The informational turn in Philosophy: any novelty in the study of Mind? - Quilici Gonzalez, Maria Eunice [UNESP]; Broens, Mariana Cláudia [UNESP]; de Moraes, Joao Antonio [UNESP] (Pontifícia Universidade Católica do Paraná (PUC-PR), 2010)
The concept of information is analyzed starting from Adams' hypothesis in The Informational Turn in Philosophy, according to which there has been a far-reaching turn in Philosophy following the publication of Turing's article "Computing Machinery and Intelligence". Adams maintains that new guidelines are being indicated in philosophical research, having the concept of "information" as the basis for treatment of classical problems, such as the relationships between mind-body, perception-action, and the nature of knowledge, amongst others. Partially agreeing with Adams, we believe, however, that his hypothesis faces difficulties, the most fundamental of which concerns the different meanings given to the concept of information. We argue that even though the concept of information underlying the mechanicist proposal of Turing, according to which "to think is to compute", is indeed being employed in Philosophy, this is not because of its mechanistic nature, but mainly due to the representationist presupposition dominant in this area. From this point of view, the informational turn in philosophy would not provide any great novelty, given that since the earliest days philosophical approaches to the nature of mind have always been mainly representationist. The novelty would not lie specifically in the Turing thesis, but in reflections on the nature of information, especially ecological information, and its relation to action.
Keywords: Ecological information; Perception-action; Mechanicism; Mental representation; Meaning